Potential of Cissampelos pareira L. Pectin as a Bioactive Compound in Moisturizing and Anti-Aging Applications - Setinee Chanpirom; Nuntawat Khat-udomkiri; Thapakorn Tree-Udom; Naphatsorn Ditthawutthikul; Nisakorn Saewan; Maria Pilar Vinardell; Tawanun Sripisut (Cosmetics, 2025)
Cissampelos pareira is a plant known for its edible and medicinal properties, with bioactive potential in various applications. This study aimed to isolate and characterize pectin from C. pareira (PCP) and assess its safety, as well as its efficacy in skin moisturizing and anti-aging effects on human volunteers. The highest yield of PCP extraction was achieved after a 45 min extraction period. Chemical composition analysis using Fourier transform infrared (FT-IR) spectroscopy confirmed the presence of a characteristic pectin structure. Optimized PCP samples revealed high methoxy pectin content, degree of esterification, and galacturonic acid concentration, along with consistent physicochemical properties. PCP exhibited antioxidant activity and showed no cytotoxicity at 1 mg/mL, and effectively reduced hydrogen peroxide-induced oxidative damage in NIH/3T3 cells. Stability assessment indicated that PCP maintains its physical appearance and total polysaccharide content after heating–cooling periods. None of the PCP formulations caused skin irritation among volunteers. In an 8-week clinical trial, subjects who used serum formulations containing 0.5% w/w and 1.0% w/w PCP showed significant improvements in skin hydration and elasticity compared to the placebo serum group. While skin smoothness, scaliness, and wrinkling also improved, these anti-aging results were not statistically significant. The results indicated PCP is a promising candidate for skin care applications due to its safety, stability, antioxidant activity, and demonstrated efficacy in enhancing skin hydration and elasticity.